Students’ Independent Work as a Factor in Forming Agency in Modern Higher Education - O. V. Besschetnova; S. N. Fomina; O. V. Besschetnova (Высшее образование в России, 2025)
The article substantiates the relevance and significance of students’ independent work in the process of obtaining higher education for the formation of agency as a broader concept, including the ability to influence the processes of one’s own life through actions and deeds; the role of independent work as a compulsory form of higher education, provided for by Federal State Educational Standard 3++, is highlighted, its importance in training personnel in conditions of increasing competition in the labor market. The purpose of the article is to establish the main types of independent work offered by modern universities and to assess their (in) effectiveness, from the point of view of students, for mastering a future profession; to identify the relationship between independent work as a component of the educational process and student agency. The article presents the results of sociological research conducted in 2023-2025, based on quantitative (online survey) and qualitative methodology (focus group method). The results of the study allow us to conclude that it is necessary to revise the forms of independent work by university teachers, to introduce new methods of working with the modern generation of students, relevant to the ongoing changes in the conditions of the digital society, in order to increase the level of their agency. The results of the study can be recommended for use in higher education to improve the quality of personnel training and enhance student motivation for professional activities in their chosen specialty.